Influence Of Job Rotation, Work Discipline, And Workload On Employee Productivity At PT. Bank Bengkulu (Persero) KC Karang Tinggi Bengkulu Tengah - Try Hendria Rahma Dewi; Janusi Waliamin; Sintia Safrianti (Journal of Research in Social Science and Humanities, 2024)
This study aims to analyze the impact of job rotation on work productivity, the impact of work discipline on work productivity, the impact of workload on work productivity, and the combined impact of job rotation, work discipline, and workload on work productivity. The research population comprises 34 employees of PT. Bank Bengkulu (Persero) KC Karang Tinggi. The sample consists of 34 respondents, selected using the census method. Data analysis was conducted using multiple regression and hypothesis testing, utilizing SPSS version 25. The results of this study concluded that job rotation does not affect employee productivity (significance 0.729 0.05), work discipline has a significant positive effect on productivity (significance 0.001 0.05), and workload does not affect productivity (significance 0.186 0.05). The combined variables of job rotation, work discipline, and workload have a significant impact on productivity (significance 0.000 0.05).